Kinetics and Mechanism of Ni(II) Chelation in Model and Real Solutions of Xylem Sap of Quercus ilex - Correia dos Santos, Margarida Maria; Alves, Sheila; de Lurdes Simões Gonçalves, Maria; Correia dos Santos, Margarida Maria; Alves, Sheila; de Lurdes Simões Gonçalves, Maria (Electroanalysis, 2007)
The kinetics of formation and dissociation of Ni(II) complexes with oxalic and citric acids was studied by cyclic voltammetry in model solutions of xylem sap of Q. ilex (the dominant tree growing on serpentine soils of Northeast Portugal) using representative concentrations, pH and ionic strength. The role of magnesium on complex formation was analyzed from solutions where Mg is present at concentration levels found in the xylem sap of Q. ilex growing on both nonserpentine and serpentine soils. Kinetics studies were also done in diluted solutions of real xylem sap samples, spiked with increasing amounts of magnesium. The values obtained for the apparent rate constants were those anticipated by the proposed model. To test the validity of the methodology and mechanisms, formation rate constants, kf (M−1 s−1) of Ni(II) complexes with citrate and oxalate were evaluated that compare with the values from Eigen mechanism.
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: 10; 1002; 200703972; Complexation; Cyclic voltammetry; doi; elan; Kinetics; Nickel; Quercus ilex; Xylem sap

Kinetics and Mechanism of Ni(II) Chelation in Model and Real Solutions of Xylem Sap of Quercus ilex - Correia dos Santos, Margarida Maria; Alves, Sheila; de Lurdes Simões Gonçalves, Maria; Correia dos Santos, Margarida Maria; Alves, Sheila; de Lurdes Simões Gonçalves, Maria (Electroanalysis, 2007)
The kinetics of formation and dissociation of Ni(II) complexes with oxalic and citric acids was studied by cyclic voltammetry in model solutions of xylem sap of Q. ilex (the dominant tree growing on serpentine soils of Northeast Portugal) using representative concentrations, pH and ionic strength. The role of magnesium on complex formation was analyzed from solutions where Mg is present at concentration levels found in the xylem sap of Q. ilex growing on both nonserpentine and serpentine soils. Kinetics studies were also done in diluted solutions of real xylem sap samples, spiked with increasing amounts of magnesium. The values obtained for the apparent rate constants were those anticipated by the proposed model. To test the validity of the methodology and mechanisms, formation rate constants, kf (M−1 s−1) of Ni(II) complexes with citrate and oxalate were evaluated that compare with the values from Eigen mechanism.
Keywords: 10; 1002; 200703972; Complexation; Cyclic voltammetry; doi; elan; Kinetics; Nickel; Quercus ilex; Xylem sap